Music, Contentious Politics, and Identity: A Cultural Analysis of “Aksi Bela Islam” March in Jakarta (2016) - Hidayatullah, Rahmat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This article examines the role of music as a repertoire of contention and as a framing device used to challenge the political legitimacy of the rulers and strengthen the collective identity of the participants in “Aksi Bela Islam” (ABI), a demonstration held in Jakarta at the end of 2016. Rizieq Shihab, one of the key actors of ABI, wrote two songs known as “Si Ahok Durjana” and “Mars Aksi Bela Islam”. This paper argues that the success of mass mobilization during ABI cannot be separated from the creative use of media and popular culture—including music. The key actors of ABI used music and popular media as framing devices to communicate cognitive meanings, mobilize potential adherents, delegitimize authorities, instill emotional feelings and awaken the collective identity of Muslims. This paper applies new social movement theory that emphasizes the significance and role of cultural factors in the dynamics of social movements.